A high-insulation and high-reliability metal soft magnetic powder core and preparation method thereof
The high-insulation and high-reliability metal soft magnetic powder core is prepared by screening and surface modification, which solves the problem that traditional insulating layer is prone to break at high pressure and high temperature, and achieves higher pressure and insulation performance, which is suitable for high-demandness. Automotive electronics applications.
Patent Information
- Application Number
- CN202411676202.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The insulating layer produced by the traditional phosphoric acid passivation process is prone to rupture during high-pressure molding and high-temperature baking, resulting in insulation deterioration, and the phosphate decomposes at high temperatures, reducing insulation characteristics.
Using a high-insulating and high-reliability metal soft magnetic powder core, a protective passivation layer and modification are formed by screening metal soft magnetic alloy powder with preset particle size and passing phosphoric acid passivation and surface modification treatment. layer to improve the pressure resistance and insulation properties of the powder. The method includes steps such as powder passivation, surface modification, insulation coating, molding, curing treatment and high-temperature heat treatment.
On the premise of combining magnetic permeability and high toughness, it can effectively improve the pressure resistance and insulation characteristics of soft magnetic powder core, reduce hysteresis loss, and improve the overall performance of the magnetic core. It is suitable for high-quality and high-reliability automotive electronics and other occasions. .
Smart Images

Figure CN119170406B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of metal soft magnetic powder cores, and in particular to a high-insulation and high-reliability metal soft magnetic powder core and a preparation method thereof. Background Art
[0002] The one-piece molded inductor is mainly composed of a metal soft magnetic composite material and a metal copper coil. It is usually prepared by embedding the coil winding in a metal soft magnetic powder through a powder metallurgy process, and then curing the adhesive by baking. Since the powder surface is coated with insulating material, the eddy current between the powder particles is hindered and the eddy current is confined inside the powder, which can greatly reduce the eddy current loss of the magnetic core.
[0003] The powder surface is coated with insulation during pre-treatment. In traditional processes, phosphoric acid liquid or phosphate liquid is usually used for passivation. Phosphoric acid, phosphate, etc. react with the metal surface to form a phosphate insulation layer. In recent years, with the gradual application of high-temperature heat treatment processes in molded inductors, it has been found that increasing the molding pressure and secondary high-temperature annealing can eliminate internal stress and significantly improve the inductance value and magnetic permeability. However, the insulation layer made by the traditional phosphoric acid passivation process has brittle phosphates generated on the surface. Not only is it easy to break during high-pressure molding, resulting in insulation degradation; but the phosphate will decompose above 600°C, resulting in coating defects, and the corresponding insulation properties will be significantly reduced. From a microscopic perspective, this is because excessive pressure will squeeze and destroy the passivation layer and insulation glue coating coated on the powder surface. At the same time, high-temperature baking accelerates the decomposition and shedding of the insulation layer. Improving the adhesion between the adhesive and the metal powder surface has become the key to solving the problem. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present application provides a high-insulation and high-reliability metal soft magnetic powder core and a preparation method thereof. The preparation method of the present application is simple, the reaction conditions are mild, the cost is low, and it can be automated for large-scale production. The high-insulation and high-reliability metal soft magnetic powder core prepared by the present application effectively improves the withstand voltage and insulation properties of the soft magnetic powder core while having both magnetic permeability and high toughness; it effectively reduces the hysteresis loss without increasing the eddy current loss, thereby reducing the overall loss of the magnetic core. The high-insulation and high-reliability metal soft magnetic powder core of the present application has excellent high insulation and withstand voltage performance, and can be used in specific occasions such as automotive electronics that require high quality and high reliability.
[0005] In a first aspect, the present application provides a method for preparing a high-insulation and high-reliability metal soft magnetic powder core, using the following technical solution:
[0006] A method for preparing a high-insulation and high-reliability metal soft magnetic powder core comprises the following steps:
[0007] S1. Screening metal soft magnetic alloy powder with a preset particle size and weighing it according to a preset mass;
[0008] S2, powder passivation: weigh the required weight of phosphoric acid, dissolve the phosphoric acid in ethanol to obtain a passivation solution, mix the passivation solution with the metal soft magnetic alloy powder, let it stand for 4 minutes and pour out the supernatant, continue to add ethanol and stir, let it stand and pour out the supernatant, repeat 3 times, the purpose is to clean the phosphoric acid remaining on the surface of the powder, spread it out to dry to a semi-wet state, dry it, and sieve it to obtain a passivation powder;
[0009] S3, surface modification: the passivation powder and the composite coupling agent are mixed, stirred evenly, dried, and sieved to obtain modified powder; wherein the composite coupling agent, by weight, comprises the following raw materials: 10-25 parts of coupling agent, 1-5 parts of adhesion promoter, 0.1-2 parts of polyvinyl pyrrolidone, 0.1-2 parts of nano zinc oxide, 0.1-2 parts of modified acetylene glycol derivatives, 0.2-4 parts of acetic acid, 60-80 parts of deionized water, the coupling agent is at least one of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, vinyl triethoxysilane, and coupling agent KR-238T; the amount of the composite coupling agent is 10-30% of the mass of the passivation powder; the drying temperature is 99-105°C, the time is 90-120min, and the sieving is through a 200-500 mesh sieve;
[0010] S4, insulation coating: after the organic solvent and the adhesive are evenly mixed, the modified powder is added thereto, stirred and mixed until a semi-wet state is obtained, sieved, and dried to obtain granulated powder;
[0011] S5, compression molding: adding lubricant to the granulated powder and stirring evenly, compression molding, cleaning the edges and corners burrs, and obtaining a blank;
[0012] S6. First heat treatment: curing the blank under air atmosphere, and naturally cooling it to room temperature to obtain a cured blank;
[0013] S7. Second heat treatment: It is carried out in a vacuum atmosphere, and the solidified blank is subjected to high-temperature heat treatment, and naturally cooled to room temperature to obtain a high-insulation and high-reliability metal soft magnetic powder core.
[0014] By adopting the above technical scheme, S1: screen the metal soft magnetic alloy powder of preset particle size and weigh it according to the preset mass. This step ensures the consistency of the quality and particle size distribution of the raw materials, which is conducive to the stability and controllability of the subsequent process. S2: Powder passivation. The metal soft magnetic alloy powder is surface treated with a passivation solution formed by mixing phosphoric acid and ethanol to form a protective passivation layer to improve the corrosion resistance and oxidation resistance of the powder. At the same time, the passivation process also helps to improve the fluidity and dispersibility of the powder. S3: Surface modification. The passivation powder and the composite coupling agent are mixed, stirred evenly, and then dried and sieved to obtain the modified powder. The composite coupling agent can enhance the compatibility and bonding force between the powder and the organic material and improve the performance of the composite material. In addition, different components in the composite coupling agent have different functions, such as the adhesion promoter can improve the adhesion between the coating and the substrate; polyvinyl pyrrolidone can improve the dispersion performance. The synergistic effect of these functions enables the modified powder to perform better in the subsequent process. S4: Insulation coating. After the organic solvent and adhesive are mixed evenly, the modified powder is added, stirred and mixed until the semi-wet state is obtained, sieved and dried to obtain granulated powder. This step is mainly to form an insulating layer on the surface of the powder to improve the insulation and pressure resistance of the material. At the same time, the formation of the insulating layer can also reduce eddy current loss and hysteresis loss, thereby improving the overall performance of the magnetic core. S5: Compression molding. The granulated powder is mixed with a lubricant and then compression molded, and the corner burrs are cleaned to obtain a rough part. This step is mainly to make the powder particles closely combine to form a dense structure and improve the mechanical properties and processing properties of the material. At the same time, the pressure during the compression molding process also helps to eliminate the pores and defects inside the powder, and further improve the density and magnetic permeability of the material. S6: First heat treatment. The rough part is cured in an air atmosphere, and naturally cooled to room temperature to obtain a cured blank. This step is mainly to make the organic solvent evaporate part of the water and residue, so that the metal soft magnetic powder core is more stable and dense. At the same time, the pressure during the curing process also helps to eliminate the stress concentration phenomenon inside the metal soft magnetic powder core and improve the strength and stability of the metal soft magnetic powder core. S7: Second heat treatment. The solidified blank is subjected to high-temperature heat treatment in a vacuum atmosphere, and naturally cooled to room temperature to obtain a high-insulation and high-reliability metal soft magnetic powder core. This step is mainly to further shrink and densify the metal soft magnetic powder core, and improve the insulation and pressure resistance of the metal soft magnetic powder core. At the same time, high-temperature heat treatment can also promote the reaction between molecules inside the metal soft magnetic powder core to enhance the chemical bonding strength and thermal stability.
[0015] Preferably, in step S1, the metal soft magnetic alloy powder is at least one of reduced iron powder, iron-nickel soft magnetic powder, iron-nickel-molybdenum soft magnetic powder, iron-silicon-aluminum soft magnetic powder, iron-silicon soft magnetic powder, and iron-silicon-chromium soft magnetic powder; the preparation process of the metal soft magnetic alloy powder is a water-gas combined atomization method, and the average particle size of the metal soft magnetic alloy powder is 2-50μm.
[0016] Preferably, in step S2, the amount of ethanol used is 6-15wt% of the mass of the metal soft magnetic alloy powder, and the amount of phosphoric acid used is 0.1-1.0wt% of the mass of the metal soft magnetic alloy powder; the mixing and stirring is specifically, stirring evenly for 5 minutes with a magnetic stirrer at a speed of 400r / min in a constant temperature environment of 30℃-80℃ to ensure that the phosphoric acid fully reacts with the surface of the metal soft magnetic alloy particle material to form a phosphate passivation layer; the drying temperature is 80-100℃, and the time is 40-60min; the screening is through a 300-500 mesh sieve.
[0017] Preferably, in step S3, the coupling agent is composed of γ-glycidyloxypropyl trimethoxysilane, vinyl triethoxysilane, and coupling agent KR-238T in a mass ratio of 3:2:3. By adopting the above technical scheme, γ-glycidyloxypropyl trimethoxysilane: this silane coupling agent contains a methoxy group that can react with the surface of inorganic matter and an epoxy group that can react with organic matter. It can improve the compatibility between inorganic filler and organic polymer, enhance interfacial bonding, and thus improve the overall performance of composite material. Vinyl triethoxysilane: this coupling agent has a vinyl group, can participate in free radical polymerization, form a cross-linked structure, and contribute to improving the thermal stability and mechanical strength of the material. At the same time, its ethoxy group can also react with the hydroxyl group on the surface of the inorganic matter to further enhance interfacial bonding. Coupling agent KR-238T is a water-based coupling agent from Kenrich Petrochemical Company in the United States, specifically a chelate solution of bis(dioctyl pyrophosphate)ethylene titanate and triethanolamine: the dioctyl pyrophosphate group mainly provides molecular hydrophobicity, which helps to improve the dispersibility of the powder in the organic medium, reduce agglomeration, heat resistance and strong chelation performance for metal ions, which is beneficial to its performance at high temperatures and can firmly adhere to metal or inorganic surfaces; the ethylene titanate group provides coupling performance and surface modification ability, which can effectively enhance the interface bonding between the filler and the polymer and improve the mechanical properties and durability of the composite material; triethanolamine provides strong chelating ability, wettability and stability, and can effectively form a stable chelate with titanate to prevent its decomposition in the aqueous system and improve the operating performance of the solution. The synergistic effect between these three coupling agents is mainly reflected in the following aspects: 1. Enhanced interface bonding: γ-glycidyloxypropyl trimethoxysilane and vinyl triethoxysilane react with inorganic and organic compatible materials through different functional groups to form a strong interface bonding force. Coupling agent KR-238T further improves the interface properties through its unique structure. 2. Improved dispersibility: Coupling agent KR-238T has good dispersibility, which can help the passivation powder to be more evenly dispersed in the deionized water solution and the modified powder in the organic solvent to avoid agglomeration, thereby ensuring the uniformity and performance stability of the material. 3. Improved thermal stability and mechanical strength: Vinyl triethoxysilane helps to form a cross-linked structure by participating in free radical polymerization, thereby improving the thermal stability and mechanical strength of the material. 4. Chemical stability: The combined use of these three coupling agents makes the final metal soft magnetic powder core have better chemical stability and can maintain stable performance in harsh environments. In summary, the synergistic effect of these three coupling agents not only enhances the comprehensive performance of the metal soft magnetic powder core, but also ensures its reliability and stability in practical applications.
[0018] Preferably, in step S4, the organic solvent is at least one of ethyl acetate, acetic acid, acetone and ethanol; the adhesive is at least one of silicone resin, organosilicon resin, polyvinyl alcohol and biphenyl phenol epoxy resin; the amount of the adhesive is 1.0-4.0% of the mass of the modified powder, the amount of the organic solvent is 8-15% of the mass of the modified powder, the drying temperature is 80-100°C, the time is 90-120min, and the sieving is through a 40-200 mesh sieve.
[0019] Preferably, in step S5, the lubricant is composed of zinc stearate, barium stearate and aluminum stearate in a mass ratio of 2:3:2; the amount of the lubricant is 0.1-0.9wt% of the mass of the granulating powder, and the compression molding pressure is 600-1500MPa.
[0020] Preferably, in step S6, the process conditions of the curing treatment are: gradually increase the temperature in the following stages: the first stage is to increase the temperature to 60°C at room temperature for 30 minutes, and the second stage is to keep the temperature for 30 minutes; the third stage is to increase the temperature to 90°C for 30 minutes and keep the temperature for 30 minutes; the fourth stage is to increase the temperature to 120°C for 30 minutes and keep the temperature for 45 minutes; the fifth stage is to increase the temperature to 180°C for the last 45 minutes and keep the temperature for 120 minutes, and then naturally cool to room temperature.
[0021] Preferably, in step S7, the vacuum degree of the vacuum is -0.1 MPa, and the process conditions of the high-temperature heat treatment are: gradually increasing the temperature in the following stages: in the first stage, the temperature is increased to 150°C at room temperature for 40 minutes, and kept warm for 40 minutes; in the second stage, the temperature is increased to 300°C for 40 minutes, and kept warm for 40 minutes; in the third stage, the temperature is increased to 450°C for 40 minutes, and kept warm for 40 minutes; in the fourth stage, the temperature is increased to 600°C for 40 minutes, and kept warm for 40 minutes; in the fifth stage, the temperature is increased to 660°C-840°C for the last 40 minutes, and kept warm for 120 minutes, and then naturally cooled to room temperature.
[0022] By adopting the above technical scheme, reducing oxidation and performing heat treatment in a vacuum environment can reduce the contact between the material and oxygen, thereby avoiding oxidation reactions and protecting the surface and internal structure of the material. The vacuum environment helps to remove impurities and gases in the material and improve the purity and performance of the material. By gradually increasing the temperature, the accumulation of internal stress in the material can be slowed down, avoiding cracks or deformation caused by excessive thermal stress caused by rapid heating. The insulation time of each temperature stage ensures that the material reaches thermal equilibrium at this temperature, so that the internal physical and chemical reactions are fully carried out, thereby improving the performance of the material. At high temperatures, the internal atomic activity of the metal soft magnetic powder core is enhanced, which helps to release internal stress, reduce coercivity, and increase density and magnetic permeability. High-temperature heat treatment can promote grain growth and recrystallization to improve the microstructure of the material, thereby improving its magnetic properties and mechanical properties. High-temperature heat treatment in a vacuum environment can reduce the oxidation and degradation of the insulating layer and maintain its good insulation properties. In summary, the vacuum degree and high-temperature heat treatment process conditions in step S7 work together to not only release the internal stress of the metal soft magnetic powder core to the greatest extent, but also optimize its microstructure, improve its magnetic permeability, density and insulation performance, thereby preparing a metal soft magnetic powder core with high insulation and high reliability.
[0023] In a second aspect, the present application provides a high-insulation and high-reliability metal soft magnetic powder core, which adopts the following technical solution:
[0024] As a general technical concept, the present application also provides a high-insulation and high-reliability metal soft magnetic powder core prepared by the above-mentioned method for preparing the high-insulation and high-reliability metal soft magnetic powder core.
[0025] In summary, the present application includes at least one of the following beneficial technical effects:
[0026] 1. Internal stress release and performance improvement: The internal stress of the metal soft magnetic powder core is not released during the curing process, and the coercive force can be reduced to the maximum extent through further high-temperature heat treatment, which can significantly release these internal stresses, and improve the density and magnetic permeability of the material. This treatment method helps to optimize the magnetic properties of the material and improve its performance in practical applications.
[0027] 2. Powder properties and cost-effectiveness: The iron-silicon-chromium alloy powder made by the water-gas combined atomization method is not only cheap and low-cost, but also has fine particle size and high sphericity, which helps to improve the magnetic properties and processing performance of the powder. At the same time, the uniform chemical composition and small segregation make this powder meet the needs of high-quality applications.
[0028] 3. The reinforcing effect of coupling agent: As a substance with an amphiphilic structure, coupling agent can form a strong bond between inorganic and organic materials, improving the bonding, adhesion and compatibility between the two. This not only improves the mechanical properties of the resin-based composite material, but also enhances the bonding strength and other properties of the resin coating, resulting in a 1+1>2 effect. In addition, a single hydroxyl group has a good dispersing and wetting function, which can significantly improve the dispersibility of the adhesive in organic solvents, help it to be more evenly coated on the powder surface, effectively improve the breakdown resistance of the integrated inductor, including the adhesion of the coil paint film, which is also well improved, enhancing the friction resistance and impact resistance of the powder, and increasing flexibility.
[0029] 4. Improvement of insulation performance: After the surface of the passivation powder is modified by the composite coupling agent, the quality reliability and insulation performance of the metal soft magnetic powder core can be significantly improved. This modified powder shows excellent performance in the preparation of high-insulation and high-reliability metal soft magnetic powder cores, especially in specific occasions such as automotive electronics that require high quality and high reliability. It has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings used in the embodiments:
[0031] Figure 1 This is the morphology of iron-silicon-chromium alloy powder. DETAILED DESCRIPTION
[0032] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0033] In the following embodiments, the iron-silicon-chromium alloy powder used is prepared by water-gas combined atomization method, and includes, by mass percentage, Si4.9wt%, Cr5.0wt%, Mn0.02wt%, and the balance is Fe. The average particle size is 10 microns, and the powder morphology is as follows: Figure 1 As shown; the adhesion promoter is a water-based epoxy compound JSC-567 purchased from Hangzhou Jessica Chemical Co., Ltd., and the coupling agent KR-238T is a water-based coupling agent purchased from Kenrich Petrochemical Company of the United States, specifically a chelate solution of bis(dioctyloxypyrophosphate)ethylene titanate and triethanolamine.
[0034] In the following preparation examples, 1 part means 10 g.
[0035] Preparation Example 1 Preparation of composite coupling agent
[0036] The composite coupling agent includes the following raw materials by weight: 12 parts of coupling agent, 2 parts of adhesion promoter, 1 part of polyvinyl pyrrolidone, 0.5 parts of nano zinc oxide, 0.5 parts of modified acetylene glycol derivatives, 0.5 parts of acetic acid, and 80 parts of deionized water. The coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0037] The preparation method of the composite coupling agent comprises the following steps: slowly dropping the coupling agent into a solution consisting of acetic acid and deionized water according to the mass fraction and mixing them evenly, and rapidly stirring the aqueous solution during the process of slowly dropping silane to prevent the formation of gel; then adding an adhesion promoter, polyvinyl pyrrolidone, nano zinc oxide and a modified acetylene glycol derivative and stirring and mixing for 60 minutes until the solution becomes completely transparent to obtain the composite coupling agent.
[0038] Preparation Example 2 Preparation of composite coupling agent
[0039] The same as Preparation Example 1, except that the coupling agent is vinyltriethoxysilane.
[0040] Preparation Example 3 Preparation of composite coupling agent
[0041] The same as Preparation Example 1, except that the coupling agent is coupling agent KR-238T.
[0042] Preparation Example 4 Preparation of composite coupling agent
[0043] The same as Preparation Example 1, except that the coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, vinyltriethoxysilane and coupling agent KR-238T in a mass ratio of 3:2:3. Example 1
[0044] A method for preparing a high-insulation and high-reliability metal soft magnetic powder core comprises the following steps:
[0045] (1) 15% ethanol and 0.2% phosphoric acid accounting for the mass of the iron-silicon-chromium alloy powder are mixed, and then the iron-silicon-chromium alloy powder is slowly added thereto, and stirred evenly for 5 minutes with a magnetic stirrer at a speed of 400 r / min in a constant temperature environment of 30° C., and the supernatant liquid is poured out after standing for 4 minutes, and ethanol is added to stir for 5 minutes, and the supernatant liquid is poured out after standing for 4 minutes, and this is repeated 3 times, in order to clean the phosphoric acid remaining on the surface of the powder, spread it out to dry to a semi-wet state, and then transferred to an oven for drying at a baking temperature of 60° C. and a baking time of 50 minutes, and passed through a 500-mesh sieve to obtain a passivated powder;
[0046] (2) Take a composite coupling agent (prepared in Preparation Example 1) accounting for 30% of the mass of the passivation powder, slowly add the passivation powder into it, stir and mix for 30 minutes, then transfer to an oven for drying at a baking temperature of 100°C for 90 minutes, and pass through a 500-mesh sieve to obtain a modified powder;
[0047] (3) 15% of the modified powder by weight of acetone and 4% of the silicone resin binder are mixed, and the modified powder is slowly added thereto, stirred and mixed until semi-wetted, sieved through a 40-200 mesh sieve, and powder with a particle size between 40 and 200 mesh is taken, and then the granulated powder is transferred to an oven for drying at a baking temperature of 80° C. for 90 min to obtain granulated powder;
[0048] (4) adding 0.5% lubricant by weight to the granulated powder, wherein the lubricant is composed of zinc stearate, barium stearate, and aluminum stearate in a mass ratio of 2:3:2, taking 2.5 g and molding it at room temperature with a molding pressure of 700 MPa, cleaning the edges and corners to obtain a blank;
[0049] (5) In an air atmosphere, the blank is placed in an oven for curing treatment to obtain a cured part; the process conditions of the curing treatment are: gradually increasing the temperature in the following stages: in the first stage, the temperature is increased to 60°C from room temperature for 30 minutes, and the temperature is kept for 30 minutes in the second stage; in the third stage, the temperature is increased to 90°C for 30 minutes and the temperature is kept for 30 minutes; in the fourth stage, the temperature is increased to 120°C for 30 minutes and the temperature is kept for 45 minutes; in the fifth stage, the temperature is increased to 180°C for the last 45 minutes and the temperature is kept for 120 minutes, and then naturally cooled to room temperature;
[0050] (6) The cured part is placed in a vacuum tube furnace, evacuated with a mechanical pump, and then subjected to high-temperature heat treatment to obtain a high-insulation and high-reliability metal soft magnetic powder core; the vacuum degree of the evacuation is -0.1 MPa, and the process conditions of the high-temperature heat treatment are: gradually increasing the temperature in the following stages: in the first stage, the temperature is increased to 150°C at room temperature for 40 minutes and kept at this temperature for 40 minutes; in the second stage, the temperature is increased to 300°C for 40 minutes and kept at this temperature for 40 minutes; in the third stage, the temperature is increased to 450°C for 40 minutes and kept at this temperature for 40 minutes; in the fourth stage, the temperature is increased to 600°C for 40 minutes and kept at this temperature for 40 minutes; in the fifth stage, the temperature is increased to 660°C for the last 40 minutes and kept at this temperature for 120 minutes, and then naturally cooled to room temperature. Example 2
[0051] The same as Example 1, except that in step (6), the temperature is raised to 720°C and maintained for 120 minutes during the last 40 minutes of the fifth stage. Example 3
[0052] The method is the same as Example 1, except that in step (6), the temperature is raised to 780°C and maintained for 120 minutes during the last 40 minutes of the fifth stage. Example 4
[0053] The method is the same as Example 1, except that in step (6), the temperature is raised to 840°C and maintained for 120 minutes during the last 40 minutes of the fifth stage. Example 5
[0054] The same as Example 1, except that in step (4), the molding pressure is 1100 MPa. Example 6
[0055] The same as Example 5, except that in step (6), the temperature is raised to 720°C and maintained for 120 minutes in the last 40 minutes of the fifth stage. Example 7
[0056] The same as Example 5, except that in step (6), the temperature is raised to 780°C and maintained for 120 minutes in the last 40 minutes of the fifth stage. Example 8
[0057] The same as Example 5, except that in step (6), the temperature is raised to 840°C and maintained for 120 minutes during the last 40 minutes of the fifth stage. Example 9
[0058] The same as Example 1, except that in step (4), the molding pressure is 1300 MPa. Example 10
[0059] The same as Example 9, except that in step (6), the temperature is raised to 720°C and maintained for 120 minutes during the last 40 minutes of the fifth stage. Embodiment 11
[0060] The same as Example 9, except that in step (6), the temperature is raised to 780°C and maintained for 120 minutes during the last 40 minutes of the fifth stage. Example 12
[0061] The same as Example 9, except that in step (6), the temperature is raised to 840°C and maintained for 120 minutes during the last 40 minutes of the fifth stage. Example 13
[0062] The same as Example 5, except that in step (2), the composite coupling agent is prepared by Preparation Example 2. Embodiment 14
[0063] The same as Example 5, except that in step (2), the composite coupling agent is prepared by Preparation Example 3. Embodiment 15
[0064] The same as Example 5, except that in step (2), the composite coupling agent is prepared by Preparation Example 4. Example 16
[0065] A method for preparing a high-insulation and high-reliability metal soft magnetic powder core comprises the following steps:
[0066] (1) 6% of the mass of the iron-silicon-chromium alloy powder and 0.1% of phosphoric acid are mixed, and the iron-silicon-chromium alloy powder is slowly added thereto, and stirred evenly for 5 minutes with a magnetic stirrer at a constant temperature of 80° C. at a speed of 400 r / min, and then transferred to an oven for drying at a baking temperature of 100° C. for 40 minutes, and passed through a 500-mesh sieve to obtain a passivated powder;
[0067] (2) Take a composite coupling agent (prepared in Preparation Example 1) accounting for 20% of the mass of the passivation powder, slowly add the passivation powder into it, stir and mix for 30 minutes, then transfer to an oven for drying at a temperature of 100°C for 120 minutes, and pass through a 500-mesh sieve to obtain a modified powder;
[0068] (3) Take 8% of the modified powder by weight of acetone and 1% of polyvinyl alcohol binder, mix them, then slowly add the modified powder into them, stir and mix until they are semi-wet, sieve through a 40-200 mesh sieve, take powder with a particle size between 40-200 mesh, and then transfer the granulated powder into an oven for drying at a baking temperature of 100° C. for 90 min to obtain granulated powder;
[0069] (4) adding 0.9% lubricant by weight to the granulated powder, wherein the lubricant is composed of zinc stearate, barium stearate, and aluminum stearate in a mass ratio of 2:3:2, taking 2.5 g and molding it at room temperature with a molding pressure of 600 MPa, cleaning the edges and corners to obtain a blank;
[0070] (5) In an air atmosphere, the blank is placed in an oven for curing treatment to obtain a cured part; the process conditions of the curing treatment are: gradually increasing the temperature in the following stages: in the first stage, the temperature is increased to 60°C from room temperature for 30 minutes, and the temperature is kept for 30 minutes in the second stage; in the third stage, the temperature is increased to 90°C for 30 minutes and the temperature is kept for 30 minutes; in the fourth stage, the temperature is increased to 120°C for 30 minutes and the temperature is kept for 45 minutes; in the fifth stage, the temperature is increased to 180°C for the last 45 minutes and the temperature is kept for 120 minutes, and then naturally cooled to room temperature;
[0071] (6) The cured part is placed in a vacuum tube furnace, evacuated with a mechanical pump, and then subjected to high-temperature heat treatment to obtain a high-insulation and high-reliability metal soft magnetic powder core; the vacuum degree of the evacuation is -0.1 MPa, and the process conditions of the high-temperature heat treatment are: gradually increasing the temperature in the following stages: in the first stage, the temperature is increased to 150°C at room temperature for 40 minutes and kept at this temperature for 40 minutes; in the second stage, the temperature is increased to 300°C for 40 minutes and kept at this temperature for 40 minutes; in the third stage, the temperature is increased to 450°C for 40 minutes and kept at this temperature for 40 minutes; in the fourth stage, the temperature is increased to 600°C for 40 minutes and kept at this temperature for 40 minutes; in the fifth stage, the temperature is increased to 660°C for the last 40 minutes and kept at this temperature for 120 minutes, and then naturally cooled to room temperature. Embodiment 17
[0072] A method for preparing a high-insulation and high-reliability metal soft magnetic powder core comprises the following steps:
[0073] (1) 9% acetone and 1.0% phosphoric acid, accounting for the mass of the iron-silicon-chromium alloy powder, are mixed, and the iron-silicon-chromium alloy powder is slowly added thereto, and stirred evenly for 5 minutes with a magnetic stirrer at a speed of 400 r / min in a constant temperature environment of 50° C., and then transferred to an oven for drying at a baking temperature of 60° C. for 60 minutes, and passed through a 500-mesh sieve to obtain a passivated powder;
[0074] (2) Take a composite coupling agent (prepared in Preparation Example 1) accounting for 20% of the mass of the passivation powder, slowly add the passivation powder into it, stir and mix for 30 minutes, then transfer to an oven for drying at a temperature of 100°C for 110 minutes, and pass through a 500-mesh sieve to obtain a modified powder;
[0075] (3) 8% of the modified powder by weight of acetone and 3% of a silicone resin binder are mixed, and the modified powder is slowly added thereto, stirred and mixed until semi-wetted, sieved through a 40-200 mesh sieve, and powder with a particle size between 40 and 200 mesh is taken, and then the granulated powder is transferred to an oven for drying at a baking temperature of 90° C. for 100 min to obtain granulated powder;
[0076] (4) adding 0.1% lubricant by weight to the granulated powder, wherein the lubricant is composed of zinc stearate, barium stearate, and aluminum stearate in a mass ratio of 2:3:2, taking 2.5 g and molding it at room temperature with a molding pressure of 1500 MPa, cleaning the edges and corners to obtain a blank;
[0077] (5) In an air atmosphere, the blank is placed in an oven for curing treatment to obtain a cured part; the process conditions of the curing treatment are: gradually increasing the temperature in the following stages: in the first stage, the temperature is increased to 60°C from room temperature for 30 minutes, and the temperature is kept for 30 minutes in the second stage; in the third stage, the temperature is increased to 90°C for 30 minutes and the temperature is kept for 30 minutes; in the fourth stage, the temperature is increased to 120°C for 30 minutes and the temperature is kept for 45 minutes; in the fifth stage, the temperature is increased to 180°C for the last 45 minutes and the temperature is kept for 120 minutes, and then naturally cooled to room temperature;
[0078] (6) The cured part is placed in a vacuum tube furnace, evacuated with a mechanical pump, and then subjected to high-temperature heat treatment to obtain a high-insulation and high-reliability metal soft magnetic powder core; the vacuum degree of the evacuation is -0.1 MPa, and the process conditions of the high-temperature heat treatment are: gradually increasing the temperature in the following stages: in the first stage, the temperature is increased to 150°C at room temperature for 40 minutes and kept at this temperature for 40 minutes; in the second stage, the temperature is increased to 300°C for 40 minutes and kept at this temperature for 40 minutes; in the third stage, the temperature is increased to 450°C for 40 minutes and kept at this temperature for 40 minutes; in the fourth stage, the temperature is increased to 600°C for 40 minutes and kept at this temperature for 40 minutes; in the fifth stage, the temperature is increased to 660°C for the last 40 minutes and kept at this temperature for 120 minutes, and then naturally cooled to room temperature.
[0079] Comparative Example 1
[0080] The same as Example 1, except that in step (2), the amount of the composite coupling agent added is 0.
[0081] Comparative Example 2
[0082] The same as Example 2, except that in step (2), the amount of the composite coupling agent added is 0.
[0083] Comparative Example 3
[0084] The same as Example 3, except that in step (2), the amount of the composite coupling agent added is 0.
[0085] Comparative Example 4
[0086] The same as Example 4, except that in step (2), the amount of the composite coupling agent added is 0.
[0087] Comparative Example 5
[0088] The same as Example 5, except that in step (2), the amount of the composite coupling agent added is 0.
[0089] Comparative Example 6
[0090] The same as Example 6, except that in step (2), the amount of the composite coupling agent added is 0.
[0091] Comparative Example 7
[0092] The same as Example 7, except that in step (2), the amount of the composite coupling agent added is 0.
[0093] Comparative Example 8
[0094] The same as Example 8, except that in step (2), the amount of the composite coupling agent added is 0.
[0095] Comparative Example 9
[0096] The same as Example 9, except that in step (2), the amount of the composite coupling agent added is 0.
[0097] Comparative Example 10
[0098] The same as Example 10, except that in step (2), the amount of the composite coupling agent added is 0.
[0099] Comparative Example 11
[0100] The same as Example 11, except that in step (2), the amount of the composite coupling agent added is 0.
[0101] Comparative Example 12
[0102] The same as Example 12, except that in step (2), the amount of composite coupling agent added is 0.
[0103] The high-insulation and high-reliability metal soft magnetic powder cores prepared in the above-mentioned embodiments and comparative examples are magnetic rings, and the outer diameter of the magnetic rings is 13 mm and the inner diameter is 8 mm.
[0104] Performance Testing
[0105] The magnetic rings prepared in Examples 1 to 15 and Comparative Examples 1 to 12 were sampled respectively. The magnetic rings were made of 0.65 mm enameled wire and wound with 14 turns. Inductance tests were performed in accordance with standard SJ20966-2006. MATS-2010SA soft magnetic material dynamic measuring device (LCR meter for short) was used to measure magnetic performance parameters such as magnetic permeability and insulation resistance of the magnetic rings. The μ value is μe=(L*Le*10000) / (4*3.1415*Ae*N2), μe: effective magnetic permeability, L: inductance (μH), Le: effective magnetic path length (mm), Ae: effective cross-sectional area (mm 2), N: number of coil turns; RS is directly tested by MICROTEST 6377 (LCRmeter); Q is the quality factor, calculated by the formula, (2*3.1415*f*L) / RS, where f: frequency (KHz), L: inductance (μH), RS: equivalent resistance (mΩ). The test results are shown in Table 1 and Table 2.
[0106] Table 1 Performance test of each embodiment
[0107]
[0108] Table 2 Performance test of each comparative example
[0109]
[0110] Analyzing the data in Table 1 and Table 2, we can see that:
[0111] 1) From the RS and Q value data in Tables 1 and 2, it can be seen that in Comparative Examples 1-4, Comparative Examples 5-8 and Comparative Examples 9-12, the RS value increases significantly and the Q value decreases significantly as the heat treatment temperature increases in the same pressure group. In Examples 1-4, Examples 5-8 and Examples 9-12, under the same pressure, as the heat treatment temperature increases, the RS and Q value fluctuate less, and the quality factor is stable, reflecting high reliability.
[0112] 2) It can be found from the IR data in Tables 1 and 2 that, under the same pressure, for Comparative Examples 1-4, Comparative Examples 5-8 and Comparative Examples 9-12, as the temperature of the heat treatment increases, the IR values all show a downward trend as a whole, and at 840°C, the IR values begin to approach 0. On the other hand, for the Example group, under the same pressure, as the temperature of the heat treatment increases, the IR values of Examples 1-4, Examples 5-8 and Examples 9-12 remain at a relatively high value, and the insulation performance is excellent.
[0113] 3) The performance comparison analysis of the magnetic rings prepared by Example 15, Example 14, Example 13, and Example 5 shows that the coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, vinyltriethoxysilane and coupling agent KR-238T in a mass ratio of 3:2:3. The synergistic effect between them not only significantly enhances the comprehensive performance of the metal soft magnetic powder core, but also ensures its reliability and stability in practical applications.
[0114] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a high-insulation and high-reliability metal soft magnetic powder core, characterized in that: The following steps are involved: S1. Screening metal soft magnetic alloy powder of a preset particle size and weighing it according to a preset mass; S2, powder passivation: weigh the required weight of phosphoric acid, dissolve the phosphoric acid in ethanol to obtain a passivation solution, mix the passivation solution with the metal soft magnetic alloy powder, let it stand for 4 minutes and pour out the supernatant; continue to add ethanol and stir, let it stand and pour out the supernatant, repeat the steps: continue to add ethanol and stir, let it stand and pour out the supernatant, 3 times, the purpose is to clean the phosphoric acid remaining on the surface of the powder, spread it out to dry until it is semi-wet, dry it, and sieve it to obtain a passivation powder; S3, surface modification: the passivation powder and the composite coupling agent are mixed, stirred evenly, dried, and sieved to obtain modified powder; wherein the composite coupling agent, by weight, comprises the following raw materials: 10-25 parts of coupling agent, 1-5 parts of adhesion promoter, 0.1-2 parts of polyvinyl pyrrolidone, 0.1-2 parts of nano zinc oxide, 0.1-2 parts of modified acetylene glycol derivatives, 0.2-4 parts of acetic acid, 60-80 parts of deionized water, the coupling agent is at least one of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, vinyl triethoxysilane, and coupling agent KR-238T; the amount of the composite coupling agent is 10-30% of the mass of the passivation powder; the drying temperature is 99-105°C, the time is 90-120min, and the sieving is through a 200-500 mesh sieve; S4, insulation coating: after the organic solvent and the adhesive are evenly mixed, the modified powder is added thereto, stirred and mixed until a semi-wet state is obtained, sieved, and dried to obtain granulated powder; S5, compression molding: adding lubricant to the granulated powder and stirring evenly, compression molding, cleaning the edges and corners burrs, and obtaining a blank; S6. First heat treatment: curing the blank under air atmosphere, and naturally cooling it to room temperature to obtain a cured blank; S7. Second heat treatment: It is carried out in a vacuum atmosphere, and the solidified blank is subjected to high-temperature heat treatment, and naturally cooled to room temperature to obtain a high-insulation and high-reliability metal soft magnetic powder core.
2. The method for preparing a high-insulation and high-reliability metal soft magnetic powder core according to claim 1, characterized in that: In step S1, the metal soft magnetic alloy powder is at least one of reduced iron powder, iron-nickel soft magnetic powder, iron-nickel-molybdenum soft magnetic powder, iron-silicon-aluminum soft magnetic powder, iron-silicon soft magnetic powder, and iron-silicon-chromium soft magnetic powder; the preparation process of the metal soft magnetic alloy powder is a water-gas combined atomization method, and the average particle size of the metal soft magnetic alloy powder is 2-50μm.
3. The method for preparing a high-insulation and high-reliability metal soft magnetic powder core according to claim 1, characterized in that: In step S2, the amount of ethanol used is 6-15wt% of the mass of the metal soft magnetic alloy powder, and the amount of phosphoric acid used is 0.1-1.0wt% of the mass of the metal soft magnetic alloy powder; the mixing and stirring is specifically, stirring evenly for 5 minutes with a magnetic stirrer at a speed of 400r / min in a constant temperature environment of 30°C-80°C to ensure that the phosphoric acid fully reacts with the surface of the metal soft magnetic alloy particle material to generate a phosphate passivation layer; the drying temperature is 80-100°C, and the time is 40-60min; the screening is through a 300-500 mesh sieve.
4. The method for preparing a high-insulation and high-reliability metal soft magnetic powder core according to claim 1, characterized in that: In step S3, the coupling agent is composed of γ-glycidyloxypropyltrimethoxysilane, vinyltriethoxysilane, and coupling agent KR-238T in a mass ratio of 3:2:
3.
5. The method for preparing a high-insulation and high-reliability metal soft magnetic powder core according to claim 1, characterized in that: In step S4, the organic solvent is at least one of ethyl acetate, acetic acid, acetone and ethanol; the adhesive is at least one of silicone resin, silicone resin, polyvinyl alcohol and phenol epoxy resin; the amount of the adhesive is 1.0-4.0% of the mass of the modified powder, the amount of the organic solvent is 8-15% of the mass of the modified powder, the drying temperature is 80-100°C, the time is 90-120min, and the screening is through a 40-200 mesh sieve.
6. The method for preparing a high-insulation and high-reliability metal soft magnetic powder core according to claim 1, characterized in that: In step S5, the lubricant is composed of zinc stearate, barium stearate and aluminum stearate in a mass ratio of 2:3:2; the amount of the lubricant is 0.1-0.9wt% of the mass of the granulated powder, and the compression molding pressure is 600-1500MPa.
7. The method for preparing a high-insulation and high-reliability metal soft magnetic powder core according to claim 1, characterized in that: In step S6, the process conditions of the curing treatment are: gradually increase the temperature in the following stages: the first stage is to increase the temperature to 60°C at room temperature for 30 minutes, and the second stage is to keep the temperature for 30 minutes; the third stage is to increase the temperature to 90°C for 30 minutes and keep the temperature for 30 minutes; the fourth stage is to increase the temperature to 120°C for 30 minutes and keep the temperature for 45 minutes; the fifth stage is to increase the temperature to 180°C for the last 45 minutes and keep the temperature for 120 minutes, and then naturally cool to room temperature.
8. The method for preparing a high-insulation and high-reliability metal soft magnetic powder core according to claim 1, characterized in that: In step S7, the vacuum degree of the vacuum is -0.1 MPa, and the process conditions of the high temperature heat treatment are: gradually increasing the temperature in the following stages, in the first stage, the temperature is raised to 150° C. from room temperature for 40 minutes, and kept at this temperature for 40 minutes; In the second stage, the temperature is raised to 300°C for 40 minutes and kept warm for 40 minutes; in the third stage, the temperature is raised to 450°C for 40 minutes and kept warm for 40 minutes; in the fourth stage, the temperature is raised to 600°C for 40 minutes and kept warm for 40 minutes; in the fifth stage, the temperature is raised to 660°C-840°C for the last 40 minutes and kept warm for 120 minutes, and then naturally cooled to room temperature.
9. A high-insulation and high-reliability metal soft magnetic powder core, characterized in that: The high-insulation and high-reliability metal soft magnetic powder core is prepared by the preparation method of the high-insulation and high-reliability metal soft magnetic powder core according to any one of claims 1-8.
Citation Information
Patent Citations
A novel inductor
CN109036785A
Preparation method of iron-based amorphous magnetic powder core
CN116435085A